Hematological changes following an Ironman triathlon: An antidoping perspective. Issue 11 (6th January 2020) - Miller, Geoffrey D.; Beharry, Adam; Teramoto, Masaru; Lai, Auriella; Willick, Stuart E.; Eichner, Daniel
Abstract: Understanding and characterizing confounding factors to the Athlete Biological Passport (ABP) is crucial for the reliable interpretation of biological profiles in the antidoping field. The physiological effects on hematological parameters and plasma volume (PV) following competition in a long‐distance triathlon, as seen in the Ironman discipline, have yet to be fully described and are the focus of this study. Complete blood count blood tests were conducted on 19 Ironman triathletes before and after an Ironman triathlon to characterize changes in hematological parameters and the effect on ABP interpretation, as it was hypothesized that changes in the plasma volume may result in the presentation of atypical ABP profiles. Baseline blood samples were collected from the athletes prior to the event, and one sample was collected per day for up to 1 week following the race. Differences were observed between the male and female athletes across multiple parameters. Most importantly to the ABP, decreases in hemoglobin concentration (HGB) and hematocrit (HCT) were identified post‐race, with the largest decreases identified on day +2. The average HGB returned to pre‐race baseline levels on day +5. Beginning 5–6 days after the race, increases in the reticulocyte percentage (Ret%) were identified. Atypical Passport Findings were identified in 32% (6/19) of the ABPs, flagged mainly due to atypical hemoglobin concentration and one instance in which the OFF‐score exceeded the adaptive model limits. These results offer a characterized timeline of hematological changes and expected shifting of plasma volume following an Ironman triathlon providing important data for the reliable interpretation of ABP profiles in this field. Abstract : Ironman triathletes had blood samples collected daily for up to one week following an event. HGB and HCT decreased significantly following the race, and levels returned to baseline 5 to 6 days later. Atypical Biological Passports were identified in 21% of the athletes.